Fair value accounting under us gaap and IFRS, and its comparison to historical cost accounting with cases from ISE - Türegün, Nida (My University, 2010)
Finansal araçları değerlendirmede geleneksel modeller arasında en yaygın kullanılanı karma model olmuştur. Karma model, hem gerçeğe uygun değer hem de tarihi maliyet hesaplamalarını kullanır. Karma modelde ticari amaçla elde tutulan araçlar Pazar fiyatı ile kaydedilir ve geriye kalan ise tarihi maliyet ile kaydedilir. Bu modelin tersine, gerçeğe uygun değer metodu geliştirilmiştir. Bu modelde finansal araçlar pazar fiyatıyla kaydedilir. Gerçeğe uygun değer muhasebesinin çeşitli endüstrilerde birçok işletme tarafından yaygın olarak kullanılması sebebiyle konuya ışık tutma amaçlı bu konu üzerinde odaklandım. Bu tezin amacı, gerçeğe uygun değer muhasebesinin yaygın olan uygulaması üzerinde araştırma yapmaktadır. Ayrıca tarihi maliyet muhasebe sistemine ve gerçeğe uygun değerle olan karşılaştırılması da yer almaktadır. Bu tezin alt bölümleri şöyledir; ilk önce gerçeğe uygun değeri Amerikan Finansal Muhasebe Standardı 157 altında göstermektedir. Sonra gerçeğe uygun değeri Uluslar arası Finansal Raporlama Standardı altında göstermektedir. Devamında gerçeğe uygun değerle, tarihi maliyet sisteminin karşılaştırılması yer almaktadır. Sonrasında gerçeğe uygun değer muhasebesi ile kredi krizleri arasındaki ilişki gösterilmektedir. Son bölüm gerçeğe uygun değer muhasebesi ile tarihi maliyet muhasebesini karşılaştıran dört ayrı örnek bulunmaktadır.

Between the traditional models to value the financial instruments, the majority used model has been the mixed model. Mixed model uses both fair value and historical cost calculations, means that instruments which are held for trading are valued at market price and rest are recorded at their historical cost. In contrast to this model, fair value method has been developed, which suggests that the financial instruments are recorded at their market value. Because the application of fair value accounting is widely spread among many businesses in various industries, I tried to focus to shed light on the subject while comparing it with historical cost. This thesis aims to review the widespread application of fair value in accounting and its application to financial instruments in particular. It also looks at the historical cost accounting and its comparison with fair value accounting. Paper is subdivided as follows: first of all it presents the fair value at FAS 157. Later, it continues with fair value under IFRS. By the following, detailed part has been taken place focusing on understanding the fair value accounting and historical cost accounting. Then the relationship with fair value accounting and credit crunch has been showed. For the last part the four cases took place to show the differences and comparison between historical cost accounting and fair value accounting. Finally, the paper is closed with conclusion.
Keywords: Finans; Muhasebe